LC-MS/MS Screening, Total Phenolic, Flavonoid and Antioxidant Contents of Crude Extracts from Three Asclepiadaceae Species Growing in Jordan - Yousef Al-Dalahmeh; Nezar Al-Bataineh; Sara S. Al-Balawi; Jamil N. Lahham; Idrees F. Al-Momani; Mohammed S. Al-Sheraideh; Abdulraouf S. Mayyas; Sultan T. Abu Orabi; Mahmoud A. Al-Qudah (Molecules, 2022)
This study aimed to evaluate the antioxidant activity and total phenolic content (TPC) and total flavonoid content (TFC) of crude extracts obtained from three Asclepiadaceae species, namely, Calotropis procera L., Peruglaria tomentosa L., and Pentatropis spiralis (Forsk.) Decne. Both butanol and aq. methanol extracts of the three species showed the highest amount of phenol and flavonoid contents, which exhibited the greatest antioxidant activity in the scavenging of 2,2-diphenyl-2-picrylhydrazyl free radical (DPPH), 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt radical cation (ABTS), ferrous chelating effect (FIC), and hydroxyl radical (HDR) assays. Phytochemical screening of the extracts revealed the presence of alkaloids, tannins, sponins, flavonoids, terpenoids, and glycosides. LC-MS analysis was carried out to identify the major compounds from each crude extract. A total of 12 phenolic compounds in the extracts of the 3 species were identified and quantified, including 9 flavonoids, 2 hydroxybenzoic acids, and 3 hydroxycinnamic acids. The current study also revealed a good correlation between total phenolic contents and the observed antioxidant activity of the crude extracts.